2016
DOI: 10.1097/coc.0000000000000101
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Prognostic Analysis of 69 Patients With Pulmonary Sarcomatoid Carcinoma

Abstract: PSC is a unique lung malignancy with poor prognosis. Patients receiving complete resection had better prognosis, likely a reflection of early-stage disease. Neither neoadjuvant nor adjuvant chemotherapy improved patient survival for those with early-stage disease. The retrospective design and small sample size limited the generalizability. Future multicenter collaborations may be necessary to determine the optimal treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
97
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(108 citation statements)
references
References 39 publications
11
97
0
Order By: Relevance
“…Although the biological behaviour and clinical course of PSC are poorly documented, some authors suggest that PSC has a dismal prognosis (11-21 % 5-year survival rate), remarkably worse than that observed in stage-matched conventional NSCLC [2][3][4]. Hybrid functional-morphological imaging such as Fluorine-18 fluorodeoxyglucose positron emission tomography/computed tomography ( 18 F-FDG PET/CT) has been extensively employed as part of routine pre-operative staging of NSCLC patients candidate to surgery [5].…”
Section: Introductionmentioning
confidence: 98%
“…Although the biological behaviour and clinical course of PSC are poorly documented, some authors suggest that PSC has a dismal prognosis (11-21 % 5-year survival rate), remarkably worse than that observed in stage-matched conventional NSCLC [2][3][4]. Hybrid functional-morphological imaging such as Fluorine-18 fluorodeoxyglucose positron emission tomography/computed tomography ( 18 F-FDG PET/CT) has been extensively employed as part of routine pre-operative staging of NSCLC patients candidate to surgery [5].…”
Section: Introductionmentioning
confidence: 98%
“…Of these, PCs, accounting for the majority of pulmonary SCs, show highly aggressive biological behaviour and resistance to chemotherapy and radiotherapy [1][2][3][4]. Meanwhile, genetic alterations eligible for molecular targeted therapies are rarely in pulmonary PC [5,6], thus demanding development of a novel therapeutic strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to other types of lung carcinoma, sarcomatoid carcinoma tends to affect older patients with a history of tobacco smoking, and a male predominance has been observed. 2,3,5,6,9,10 Treatment is the same as for other lung carcinoma with non-small cell morphology, but sarcomatoid carcinoma tends to have a poor prognosis even in early-stage disease. 8 Substantial advancements in the treatment of lung cancer have occurred during the past decade, predominantly in adenocarcinomas.…”
mentioning
confidence: 99%
“…[11][12][13][14] Although the molecular characteristics of the more common subtypes of lung carcinoma have been extensively studied, the molecular features and presence of targetable genetic abnormalities in pulmonary sarcomatoid carcinoma are largely unknown. The currently available chemotherapy for sarcomatoid carcinoma is highly ineffective, [4][5][6][7] and thus targeted therapy is a very attractive therapeutic option to improve outcome. A recent study reported frequent MET exon 14 skipping mutations in pulmonary sarcomatoid carcinomas, which may be targetable, in addition to mutations in other genes without currently available targeted therapy, including TP53 and KRAS.…”
mentioning
confidence: 99%
See 1 more Smart Citation